Pengukuran Tingkat Kapabilitas Tata Kelola E-Learning Menggunakan COBIT 5.0 Pada SMK TI Bali Global Jimbaran - I Wayan Gede, Narayana; M Samsudin; I W Bandem W.P.N; Komang Eka Andra Tri Dharma (Elkom: Jurnal Elektronika dan Komputer, 2024)
E-Learning becomes a platform which supports technology-based learning on many aspects. The usage of E-Learning becomes the main choice especially in education world. SMK TI Bali Global Jimbaran, which is a middle level vocational school, utilizes this platform in its learning process. In its implementation process, there needs to be a precise and thorough supervision to ensure that the system runs according to business goals. This mapping is conducted to know the process used for measurements. This mapping is done by framework with COBIT 5 by applying PAM (Process Assessment Model), which is adjusted with the condition on research place. The activity measurement are derived from several domains on COBIT 5 with mapping process based on the business goals and institution goals. The domains used are EDM03, AP003, BAI07, DSS05 and MEA01. The results of governance measurement process on current capability level is on level 4 (predicable process) and the expected capability level is on level 5 (Optimizing Process) which has gap value of 2 level.